Didactic strategy for the use of GeoGebra software in learning movement and force in High School students - Cevallos-Molina, Eddy Ronaldo; Mestre-Gómez, Ulises (Educação Matemática Debate, 2023)
The Ecuadorian curriculum promotes the use of simulations for the teaching of Physics. In this research, a didactic strategy is designed for the use of GeoGebra in the learning of the concepts of movement and force for the students at the High School. In this qualitative-exploratory study, a test and a survey were applied to a sample of students at this level, as well as an interview with the Physics teacher to diagnose the availability of resources and the difficulties in learning Physics. It was found that students perceive the subject as difficult to learn, have deficiencies in their mathematical skills, frequently do not master the previous contents and do not understand the relationship between the variables involved in physical phenomena. Subsequently, a didactic strategy was developed that includes simulations so that students significantly understand the phenomena related to these contents.